Peningkatan Prestasi Belajar Pai Melalui Metode Demonstrasi pada Siswa Kelas Ia Sd Negeri 025 Cikutra - Siti Faridah (Jurnal Syntax Admiration, 2023)
Student success in learning is influenced by several factors, one of which is the method used by teachers in teaching. In fact, in learning teachers use the classical method, namely lectures, so that students are less active in learning and learning achievement is less satisfactory, therefore it is necessary to use other methods to improve learning achievement. This study is to determine whether the demonstration method can improve student achievement about compulsory prayer material in Class IA students of SD Negeri 025 Cikutra Kota Bandung. This classroom action research uses a demonstration method by demonstrating or demonstrating to students a process, situation that is being studied so that the process of student acceptance of the lesson will be more memorable in depth. This research is a PTK with 2 cycles through 4 stages, namely planning, implementation, observation and reflection. The research was conducted at SD Negeri 025 Cikutra Kota Bandung, with the help of 1 collaborator or colleague, namely Nirmala Ayuningtyas, S.Pd. The subjects of this study were 30 students. The hypothesis proposed is that if the demonstration method can be used properly, it can improve the learning achievement of PAI subject students in grade IA students of SD Negeri 025 Cikutra Kota Bandung. The success indicator is 70% with a KKM of 70. Data collection techniques by observation. Data analysis techniques with formulas to find out the average value and percentage.